Effect of Spacing and Application of Foliar Nutrients on Growth and Yield of Black Pepper (Piper nigrum) - Swarnapriya, R. (University of Jaffna, 2020)
An experiment was conducted at Horticultural Research Station, Pechiparai, Tamil Nadu, India during 2014 - 2017. The objective of the study was to find out the effect of different spacing and foliar nutrients on the growth and yield of black pepper. The variety Panniyur-1 (Bush type) was selected for the study. The soil of the experimental area is red laterite and this experiment was laid out in Factorial Randomized Block Design with three replicates. Pepper is a vine trained in support trees grown at a spacing of 3 X 3 m. In this study three closer spacing's (S - 2.0 x 2.0 1 m, S - 1.5 x 1.5m, S - 1.0 x 1.0m) and the foliar nutrients (F -Humic %, 2 3 1 acid@0.2 F – Panchagavya@3.0%, F -NPK 19:19:19 spray@0.2%, F -GA3 spray@20ppm 2 3 4 and F – Control -Water spray) were used as treatment combinations. Soil application 5 of 1.0: 0.5: 2.0 g of NPK per plant at bi monthly intervals were applied uniformly to all plants as per the recommended package of practices of Tamil Nadu. The foliar nutrients as per the treatment specification were imposed for achieving a rapid response and were given in fortnightly intervals commencing from third month after planting. Observations were recorded on the height of the bushes at the time of harvest, number of spikes/bush, spike length, number of berries/spike. The green berry yield was also recorded.Among the different treatments S F (spacing 2.0 x 2.0mand NPK 1 3 19:19:19 spray @0.2%) recorded the highest number of spikes per vine (143.10), spike length (16.24 cm) and the highest green berry yield of 1.1 kg/bush and it was significantly superior over the other treatment combinations.
Keywords: Bush black pepper; Foliar application; Panniyur – 1; Spacing; Tamil Nadu, India